Diagnosing Appendicitis in Pregnancy Via Ultrasonography - Mangal, Rohan (Cureus, 2019)
The authors present a case of acute appendicitis during a first trimester pregnancy. Appendicitis in pregnancy is especially dangerous because perforation of the appendix increases the likelihood of maternal and fetal morbidity significantly. For this reason, it is important to diagnose and treat suspected appendicitis in pregnancy as soon as possible. The patient was diagnosed with appendicitis via a transabdominal ultrasound. She was provided antibiotics and underwent a laparoscopic appendectomy and recovered without complications.